Kajian Dampak Beroperasinya Mall Boemi Kedaton Terhadap Pola Pergerakan Lalu Lintas pada Kawasan Kedaton dan Sekitarnya - Riana, Eva (UNIVERSITAS LAMPUNG, 2019)
Jalan Teuku Umar - Sultan Agung No. 1. Bandar Lampung. This area is one of the international and regional trade and services areas that have been established with the Regional Regulation of Bandar Lampung City No. 10 year 2011 about Spatial Planning for the Year 2011-2030. The area is also closed to the higher education area surrounding Jalan Zainal Abidin Pagar Alam, Gedong Meneng and Rajabasa which have universities, schools, courses and tutoring that influence the rise / pull of travel in Kedaton and surrounding area . Based on calculation and analysis, it can be seen that the development of Mall Boemi Kedaton has no significant impact on the performance of the road network in Kedaton and surrounding areas for the existing condition, it can be seen from the level of service in all road segments in the study area has a V/C Ratio < 0,75. While the average degree of saturation obtained from signaled intersection analysis and not signaled > 0,75 so it is necessary to optimize the intersection performance by changing the junction cycle time that is adjusted to traffic volume and intersection management where the intersection using LTOR system (Left Turn On Red ) to be without LTOR. For the next 5 years, roads that are estimated to experience poor performance are Jalan Sultan Agung, Jalan Urip Sumoharjo, Teuku Umar Street and Jalan Pagar Alam, while for the intersection there will be problems due to the degree of saturation > 1.